Solar Charge Controller with Maximum Power Point Tracking for Low-Power Solar Applications - Tomy Abuzairi; Wing Wira Adimas Ramadhan; Kresna Devara (International Journal of Photoenergy)
Solar Charge Controller (SCC) with Maximum Power Point Tracking (MPPT) is needed to extract maximum energy from photovoltaic. However, a SCC device with MPPT technology feature is expensive on the market due to the requirements for a high-power system. On the other hand, in lower power applications such as IoT sensors, solar street lights, and wireless communication nodes, these types of controllers can be produced at a lower cost. In this study, the design of a low-cost SCC was conducted using the MPPT technology for low-power solar applications. The SCC is designed based on the Arduino microcontroller, which has the role of controlling the circuit and producing PWM signals to regulate the DC-DC converter. Several tests were conducted to validate the efficiency of the MPPT algorithm. The SCC device succeeded in increasing efficiency up to 52% on the low irradiance level.